2015
DOI: 10.1007/s11356-015-4521-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of arbuscular mycorrhizal fungi status and heavy metal accumulation characteristics of tree species in a lead–zinc mine area: potential applications for phytoremediation

Abstract: To select suitable tree species associated with arbuscular mycorrhizal fungi (AMF) for phytoremediation of heavy metal (HM) contaminated area, we measured the AMF status and heavy metal accumulation in plant tissues in a lead-zinc mine area, Northwest China. All 15 tree species were colonized by AM fungi in our investigation. The mycorrhizal frequency (F%), mycorrhizal colonization intensity (M%) and spore density (SP) reduced concomitantly with increasing Pb and Zn levels; however, positive correlations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 79 publications
4
40
0
Order By: Relevance
“…Zn is an essential metal for plant growth and plays an important role in photosynthesis and enzyme composition for protein synthesis [46]; however, Pb is a non-essential element and has toxic effects on plant growth (membrane damage and oxidative stress) [47]. Therefore, plants may develop their own strategy to survive in HM polluted soil: reducing availability of toxic HM (Pb) in rhizosphere and preventing the translocation of Pb from soil to the aerial parts of plants, which was consistent with our previous study [24,31]. Various studies have indicated that plant root exudates could react with HM ions and affected metal solubility, mobility and phytoavailability [48].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Zn is an essential metal for plant growth and plays an important role in photosynthesis and enzyme composition for protein synthesis [46]; however, Pb is a non-essential element and has toxic effects on plant growth (membrane damage and oxidative stress) [47]. Therefore, plants may develop their own strategy to survive in HM polluted soil: reducing availability of toxic HM (Pb) in rhizosphere and preventing the translocation of Pb from soil to the aerial parts of plants, which was consistent with our previous study [24,31]. Various studies have indicated that plant root exudates could react with HM ions and affected metal solubility, mobility and phytoavailability [48].…”
Section: Discussionsupporting
confidence: 85%
“…In our previous investigation, R. pseudoacacia had been identified as lead/zinc tolerant dominant tree species widely distributed in HM contaminated soils in Feng County [24]. This tree was considered as a suitable candidate for phytoremediation owing to its developed root system, high biomass productivity, environmental stress tolerance and ability of atmospheric nitrogen fixation [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mumtaz et al [83] demonstrated the potential of fungi like Aspergillus, Cryptococcus, Penicillium and Curvularia for bioremediation of uranium contaminated soils which was attributed to their uranium binding ability. Symbiotic association of AM fungi with the roots of plants promoted immobilization of heavy metals and hence provided ability to plants to grow in metal-contaminated soils as observed in case of enhanced Cd tolerance of plants [84,85]. Further enhancement in remediation potential of toxic compounds by fungi could be achieved by certain pre-treatments.…”
Section: Bioremediation Of Heavy Metalsmentioning
confidence: 98%
“…R. pseudoacacia is frequently found in HM contaminated areas and it may serve as an indicator of Pb pollution (Serbula et al, 2012). R. pseudoacacia plants are well grown and commonly colonized by AMF such as F. mosseae in the Qiandongshan lead–zinc polluted area (Yang et al, 2015b,c). Recent studies have shown that photosynthesis and antioxidant enzymes (e.g., superoxide dismutase and ascorbate peroxidases) in the leaves of R. pseudoacacia are enhanced by F. mosseae under Pb stress (Yang et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%